The Society for Obstetric Anesthesia and Perinatology Coronavirus Disease 2019 Registry: An Analysis of Outcomes Among Pregnant Women Delivering During the Initial Severe Acute Respiratory Syndrome Coronavirus-2 Outbreak in the United States. Issue 1 (23rd March 2022) - Katz, D.; Bateman, B.T.; Kjaer, K.; Turner, D.P.; Spence, N.Z.; Habib, A.S.; George, R.B.; Toledano, R.D.; Grant, G.; Madden, H.E.; Butwick, A.J.; Lynde, G.; et al.
Abstract : ( Anesth Analg . 2021;133:462–473. doi: 10.1213/ANE.0000000000005592) From the beginning of the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) outbreak to January 17, 2021, there was an interest concerning and growing research on pregnancy and SARS-CoV-2, but little data had been gathered and analyzed comparing obstetric patients with and without the virus with regards to anesthetic management. The Society for Obstetric Anesthesia and Perinatology (SOAP) coronavirus disease 2019 (COVID-19) registry was made primarily to better understand anesthetic management and obstetric outcomes in women with and without SARS-CoV-2 during hospital delivery at widespread-testing institutions.